جودة الخدمة في الانترنت - جركس تاج الدين; معترماوي عدنان; ناصر غسان (Latakia University Journal -Engineering Sciences Series, 2019)
افتقرت شبكة الانترنت في بدايتها جودة الخدمة، واعتمدت نموذج أفضل جهد الذي يعمل على قاعدة القادم أولاً يتم تخديمه أولاً (FIFO)، ولكن مع ظهور التطبيقات الشبكية بالزمن الحقيقي والتنوع الكبير في حجم تطبيقات الانترنت أصبح من الضروري دعم عدة مستويات من جودة الخدمة، وتقديم أصناف مختلفة من حركات السير. يقدم هذا البحث نظرة عامة وشاملة على مختلف جوانب جودة الخدمة وفق منهجية جديدة تقوم على دراسة جودة الخدمة في الانترنت وتحليلها وتقويمها، وإجراء مقارنة بين هيكليتي جودة الخدمة في الانترنت؛ كما يعرض البحث نتائج محاكاة تساعد في استكشاف نموذج جودة الخدمة الذي يمكن استخدامه والتوليفات التي يمكن تقديمها لتحسين بارامترات جودة الخدمة باستخدام تقنيات مختلفة. وفي نهاية البحث يتم تقديم استنتاجات وتوصيات مناسبة تساهم في تطوير جودة الخدمة في الانترنت وتحسينها. Internet network was lacked to the QoS at the beginning and it was based on the best effort model that works on the base: First-In First-Out (FIFO). However, with the creation of real time network applications and the big diversity of Internet application volume, the support of QoS levels and providing different traffic classes became necessary. This paper presents review over different sides of QoS according to a new method that is based on investigating, analyzing and evaluating QoS in the Internet, and introduces a comparison of architectures of QoS in the Internet. Also in this paper simulation results are presented, which explore what kind of QoS the combination of Integrated and Differentiated Services can offer using different techniques for improving and enhancing parameters of QoS. At the end of paper, some suitable conclusions and recommendations for developing and improving QoS in the Internet were provided.